Obesity and diet contents of protein and fat are associated with underreport of energy at pregnancy - Maria Beatriz Trindade de Castro; Camila Benaim; Ilana Eshriqui; Thatiana de Jesus Pereira Pinto; Camilla Medeiros Macedo da Rocha; Ana Amélia Freitas-Vilela; Gilberto Kac; Ana Beatriz Franco-Sena (Revista Brasileira de Saúde Materno Infantil, 2023)
Abstract Objectives: to evaluate the association of pre-pregnancy and current body mass index and the density of dietary macronutrients on underreporting of energy intake at pregnancy. Methods: cross-sectional analysis of 327 postpartum women from the city of Mesquita, in Rio de Janeiro. A food frequency questionnaire was administered at maternity ward having the last six months of the pregnancy as the time frame. Energy balance was considered as the outcome, and it was calculated as the division of energy intake by basal metabolic rate (underreport <1.35). Multivariate logistic regression was applied to test the associations between body mass index (pre-gestational and postpartum) on energy balance (underreport or not). Dietary density of protein (4th quartile), carbohydrate (1st quartile) and fat intake (1st quartile) were tested. Results: mean energy intake was 2,894 kcal and near of 25% of the women were considered as underreported during pregnancy. Obese women had higher chance (OR=1.90; CI95%=1.09-3.33) of being underreported at pregnancy. Underreported women presented greater chance of report dietary intake with higher contents of protein (OR=2.37; CI95%=1.37-4.09) and lower density of fat (OR= .81; CI95%=1.04-3.15). Conclusion: underreported pregnant women had higher chance of report great and lower amounts of protein and fat dietary densities.